The role of dietary inflammatory index and fruit–vegetable variety in body fat accumulation among adolescents - Lourena, Crysty; Tamtomo, Didik Gunawan; Wiboworini, Budiyanti (Alma Ata University Press, 2025)
ABSTRAK Latar Belakang: Pada tahun 2023, sebanyak 8,8% remaja Indonesia mengalami overweight dan 2,9% mengalami obesitas. Hal itu dapat terjadi karena pola makan tidak sehat, terutama makanan yang memiliki potensi inflamasi tinggi sehingga mempengaruhi lemak tubuh. Dietary Inflammatory Index (DII) merupakan cara untuk mengetahui tingkat potensi inflamasi makanan. Besarnya nilai potensi inflamasi makanan serta bervariasinya konsumsi buah dan sayur dapat mempengaruhi komposisi lemak tubuh remaja.Tujuan: Mengetahui hubungan skor inflamasi makanan dan variasi konsumsi buah sayur terhadap lemak tubuh pada remaja.Metode: Penelitian menggunakan observasional analitik dengan desain cross-sectional. Sampel dipilih menggunakan metode multistage random sampling dan terpilih 150 remaja berusia 15-18 tahun. Pengambilan data lemak tubuh menggunakan Bio Impedance Analysis (BIA) dan data asupan makan menggunakan Semi Quantitative Questionnaire (SQ FFQ). Penelitian dilakukan di Surakarta pada bulan Mei-Juni 2024. Hasil: Variasi buah sayur pada remaja memiliki rentang skor 0-18 dan skor Dietary Inflammatory Index DII -1,91 hingga 2,39. Hasil uji Spearman menunjukkan hubungan yang signifikan antara skor inflamasi makanan dengan persen lemak tubuh tubuh (r = 0,18, p=0,026), namun tidak ditemukan hubungan yang signifikan antara konsumsi variasi buah sayur dengan persen lemak tubuh (r= 0,006, p=0,941).Kesimpulan: Tingginya potensi inflamasi makanan berhubungan dengan peningkatan lemak tubuh remaja, namun sayur buah tidak berhubungan dengan lemak tubuh remaja.KATA KUNCI: asupan sayur buah; asupan sayur buah; dietary inflammatory index; lemak tubuh; remajaABSTRACTBackground: In 2023, 8.8% of Indonesian teenagers were overweight, while 2.9% were obese. Many teens are overweight or obese because they eat unhealthy, inflammation-causing foods that increase body fat. The Dietary Inflammatory Index (DII) is a method used to determine the level of inflammatory potential in food. The level of the inflammatory potential value in food and the variation in fruit and vegetable consumption can affect the body fat composition of adolescents.Objective: To determine the relationship between the inflammatory score of food and the variation in fruit and vegetable consumption on adolescent body fat.Method: This study used an analytical observational method with a cross-sectional design. The sample of 150 adolescents aged 15-18 was selected using multistage random sampling. Adolescents’ body fat was measured using Bio-Impedance Analysis (BIA) and their dietary intake was assessed using the Semi-Quantitative Questionnaire (SQ-FFQ). The research was conducted in Surakarta from May to June 2024. Results: The variation of fruits and vegetables in adolescents has a score range of 0-18 and a DII score of -1.91 to 2.39. Spearman correlation showed that the DII score positively correlates with body fat percentage (r = 0.18, p = 0.026). However, no significant effect was found between fruit and vegetable variety consumption on body fat percentage (r =0.006 p=0.941). Conclusion: Foods with high inflammatory potential may increase body fat in adolescents, while fruit and vegetable variety does not. The health department should offer guidelines to help the community, especially adolescents, choose non-inflammatory foods and avoid high-inflammatory ones.KEYWORDS: dietary inflammatory index; fruit and vegetable intake; body fat; adolescents